Peran Pemerintah Desa Sirambas Kabupaten Mandailing Natal Dalam Meningkatkan Perekonomian Masyarakat Dari Objek Wisata Sampuraga - Dodi Kurniawan; Walid Musthafa Sembiring; Nina Angelia (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2023)
Sirambas Village is located in Panyabungan Barat Subdistrict, Mandailing Natal Regency, known for its Sampuraga tourist attraction. Within the Sampuraga tourist site, there are intriguing features such as the famous Sampuraga hot springs, which have gained legendary status and recognition in various countries. There are several hot spring spots where corn and eggs can be boiled until cooked, and stone therapy that releases steam from the pores of the stones, claimed to eliminate viruses from the body. This presents a significant opportunity for the government of Sirambas Village to create employment opportunities for the local community through the Sampuraga tourist attraction. The focus of this research is the village government's role and involvement in this context. The author utilizes the role theory by Santosa, Arimbi, and Horoepoetri, which encompasses policies, strategies, and communication, to assess the extent of the government's role in improving the local community's economy through the Sampuraga tourist attraction in Sirambas Village, Mandailing Natal Regency. The research adopts a qualitative descriptive method, employing techniques such as interviews, observations, and documentation. The findings reveal that the government of Sirambas Village, Mandailing Natal Regency, carries out various activities, including socializing with the local community and the tourism department, encouraging residents to establish businesses, managing parking areas, and maintaining cleanliness in the Sampuraga tourist site. However, there are hindering factors, such as limited human resources and a low level of community involvement.